Bahasa kesusasteraan klasik Kedah - Asmah Haji Omar 1940-; Dewan Bahasa dan Pustaka (Kuala Lumpur Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1995)
Structure of language in Kedah classical literature.
Includes bibliographical references (pages 265-267) and index.
In Malay.
Keywords: Malay language -- Dialects -- Malaysia -- Kedah -- Grammar